2015
DOI: 10.1021/cs5020783
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Regime Change in the Tandem Dehydrative Aromatization of Furan Diels–Alder Products

Abstract: Renewable production of p-xylene from [4 + 2] Diels− Alder cycloaddition of 2,5-dimethylfuran (DMF) and ethylene with H−Y zeolite catalyst in n-heptane solvent is investigated. Experimental studies varying the solid acid catalyst concentration reveal two kinetic regimes for the p-xylene production rate: (i) a linear regime at low acid site concentrations with activation energy E a = 10.8 kcal/mol and (ii) a catalyst-independent kinetic regime at high acid site concentrations with activation energy E a = 20.1 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
139
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(150 citation statements)
references
References 31 publications
(70 reference statements)
7
139
2
Order By: Relevance
“…d Reaction barriers and adsorption energies are tabulated in units of kcal/mol. Adjustments to parameters shown in parantheses, consistent with the adjustments made in the prior work 37 and within expected computational error…”
Section: Diels-aldersupporting
confidence: 70%
See 1 more Smart Citation
“…d Reaction barriers and adsorption energies are tabulated in units of kcal/mol. Adjustments to parameters shown in parantheses, consistent with the adjustments made in the prior work 37 and within expected computational error…”
Section: Diels-aldersupporting
confidence: 70%
“…37 This model can be re-derived for the rate of toluene production from 2-methylfuran and ethylene and reparameterized using values obtained from the QM/MM calculations (Table 3) Figure 4d). 40 ring in methylfuran increases the number of possible side reactions, as compared to the DielsAlder cycloaddition of 2,5-dimethylfuran and ethylene.…”
Section: Main Reactionmentioning
confidence: 99%
“…BTX aromatics are particularly utilized as precursors in the production of polystyrene, polyurethane, and polyethylene terephthalate (PET), for whose demand has increased globally [5]. Recently, a thermochemical route to produce renewable BTX aromatics from biomass-derived furans (i.e., 2,5-dimethylfuran (DMF), 2-methylfuran (MF), furan) and ethylene via Diels-Alder cycloaddition and subsequent dehydration reactions, has been proposed using solid Brønsted and Lewis acid catalysts [6][7][8][9][10][11][12][13][14][15][16][17]. Because ethylene can also easily be obtained by the dehydration of bio-ethanol [18], this route can be considered as a fully sustainable process for the production of BTX chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…The yield of p-xylene increased linearly with the density of acid sites. It has been shown that the initial Diels-Alder reaction of DMF and ethylene proceeds uncatalyzed and the overall rate of p-xylene formation is controlled by the catalyzed dehydration of the cycloadduct for H-Y zeolite and WO x -ZrO 2[11,13,15,22]. The rate of p-xylene formation increased with an increase in the concentration of Brønsted acid sites[22] .…”
mentioning
confidence: 99%
“…It has been shown that the initial Diels-Alder reaction of DMF and ethylene proceeds uncatalyzed and the overall rate of p-xylene formation is controlled by the catalyzed dehydration of the cycloadduct for H-Y zeolite and WO x -ZrO 2[11,13,15,22]. The rate of p-xylene formation increased with an increase in the concentration of Brønsted acid sites[22] . Thus, the variation of the yield of p-xylene with different Si/Al ratios of the SAAs can be explained by the dependence of the p-xylene production rate on the concentration of the Brønsted acid sites.In addition to the effect of acid site concentrations, the change of the p-xylene yield over SAAs with different Si/Al ratios may be partially caused by the different deactivation performances of the SAAs because the deactivation of the catalysts occurred during the reaction by the formation of heavy oligomers on the catalyst surface (SeeFig.…”
mentioning
confidence: 99%